Modification of the method of hierarchy analysis based on the elimination of the subjectivity of expert assessments using the example of choosing a rational option for a belt conveyor drive system - Goncharov K.A. (Научно-технический вестник Брянского государственного университета)
The expert assessment method underlies most decision-making methods in the technical field of activity, from the search for rational design solutions to issues of industrial safety of hazardous production facilities, which is embodied in the form of regulatory documents governing the implementation of a risk-oriented approach to problem solving in the specified areas. The subjectivity of the expert assessment method can often lead to decisions that are objectively not rational in a specific design situation. This article considers a modification of the superstructure of the criteria weight assessment level of the hierarchy analysis method based on statistical processing of a set of possible combinations of criteria priorities using the example of choosing a rational option for a belt conveyor drive system, which is a direct replacement for the expert assessment method and paired comparisons at this hierarchy level. It is shown that when taking into account the proposed modification and paired comparison at the first level of the hierarchy of clearly defined values of options within each criterion (characteristics of technical objects), the method of paired comparisons is excluded from the structure of the methodological apparatus of the hierarchy analysis method, which makes it possible to single out the obtained set of results into a separate decision-making method.